Writing an Ethnic Identity between Worlds: Claiming and Maintaining a Franco-American Self - LeBlanc, Caroline (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2011)
Euro-heritage immigrants of all backgrounds entering the U.S. at the threshold of the twentieth century experienced much the same religious, language, and ethnic oppression. Calling on facts about the author’s French-Canadian and Acadian families, this paper explores some reasons for the relative lack of visible success, prominence, and unity among Franco-American individuals and communities, when compared to Italian and Irish cohort groups. In seeking to identify what dynamics within the Franco-American community and psyche might have contributed this situation, the author explores two important differences between Franco-American and other cohort immigrant groups. These are the inherited, conservative French-Canadian policy of “la survivance” and the geographical proximity of Canada, the most recent Mother Country for French-Canadian immigrants. Calling on precepts of Bowen Family Systems Theory, Jungian Theory, and publications about Franco-Americans in the Northeastern U.S., the author offers a psychosocial perspective on these questions. Relevant excerpts from interviews with other published Franco-American poets expand the discussion. These excerpts focus on the issues of language and religious affiliation, which remain the two most contentious criteria for inclusion in the Franco-American community. The paper concludes with information on university and internet resources that create new opportunities for a more inclusive, visible, and viable Franco-American community and network within the United States, as well as between the United States and Canada.